Estimation of demand systems based on elasticities of substitution - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
This paper develops a model for demand-system estimations, whose coefficients are own-price Marshallian elasticities and elasticities of substitution between goods. The model satisfies the homogeneity, symmetry and, eventually, adding-up restrictions implied by consumer theory, and is primarily useful for the estimation of the demands of several goods of the same industry or group of products. The characteristics of the model are compared to other existing alternatives (logarithmic, translog, AIDS and QUAIDS demand systems). The model is finally applied to estimate the demands for several carbonated soft drinks in Argentina, and its results are presented, together with the ones obtained with the other estimation methods.
Keywords: C30; C51; D12; L66; 330; Demand Systems; Elasticity of Substitution; Simultaneous Equations; Carbonated Soft Drinks; Nachfragesystem; Substitutionselastizität; Theorie; Erfrischungsgetränk; Argentinien